ORGANIZATIONAL PEDAGOGICAL ACTIVITY AND TRAINING FUTURE TEACHERS TO EDUCATIONAL WORK IN SUMMER CHILDREN'S HEALTH CAMPS (Pedagogy of Higher and Secondary Education, 2011)
The article highlights the organizational pedagogical activity in a summer camp for children.